Obesogenic environment by excess of dietary fats in different phases of development reduces spermatic efficiency of wistar rats at adulthood: correlations with metabolic status - Reame, Vanessa [UNESP]; Pytlowanciv, Eloisa Zanin [UNESP]; Ribeiro, Daniele Lisboa; Pissolato, Thiago Feres [UNESP]; Taboga, Sebastiao Roberto [UNESP]; Goes, Rejane Maira [UNESP]; Pinto-Fochi, Maria Etelvina [UNESP] (Oxford University Press (OUP), 2014)
This study compares the impact of obesogenic environment (OE) in six different periods of development on sperm parameters and the testicular structure of adult rats and their correlations with sex steroid and metabolic scenario. Wistar rats were exposed to OE during gestation (O1), during gestation/lactation (O2), from weaning to adulthood (O3), from lactation to adulthood (O4), from gestation to sexual maturity (O5), and after sexual maturation (O6). OE was induced by a 20% fat diet, and control groups were fed a balanced diet (4% fat). Serum leptin levels and adiposity index indicate that all groups were obese, except for O1. Three progressive levels of impaired metabolic status were observed: O1 presented insulin resistance, O2 were insulin resistant and obese, and groups O3, O4, and O5 were insulin resistant, obese, and diabetic. These three levels of metabolic damage were proportional to the increase of leptin and decreased circulating testosterone. The impairment in the daily sperm production (DSP) paralleled these three levels of metabolic and hormonal damage being marginal in O1, increasing in O2, and being higher in groups O3, O4, O5, and O6. None of the OE periods affected the sperm transit time in the epididymis, and the lower sperm reserves were caused mainly by impaired DSP. In conclusion, OE during sexual maturation markedly reduces the DSP at adulthood in the rat. A severe reduction in the DSP also occurs in OE exposure during gestation/lactation but not in gestation, indicating that breast-feeding is a critical period for spermatogenic impairment under obesogenic conditions.